Chapter Insegnare (lessico del)le microlingue: specificità nell'insegnamento e nelle strategie didattiche - BALLARIN, Elena (Strumenti per la didattica e la ricerca, 2021)
In the teaching of micro-languages, vocabulary teaching constitutes the main challenge for teachers. The ideal micro-language teacher should be a competent professional both in the discipline of specialization and in the corresponding micro-language. This type of teacher should be a graduate in languages with specialized training also in a different disciplinary sector, or a specialist with language and teacher training. In the Italian educational reality the micro-language teacher is (it is hoped) a graduate in languages - but not necessarily specialized in language teaching. The teacher-learner relationship is vitiated by a sense of imperfection due to the teacher's lack of training in the discipline concerned and the learner's lack of training in the language. This limit can be overcome in the teaching of scientific-professional micro-languages by means of a collaborative teaching model. The challenge becomes more difficult, when teaching disciplinary micro-languages, because learners do not have full mastery of the non-language discipline they are acquiring. This contribution aims to explore the specificities that arise when different didactic realities manifest critical aspects.